Bounded below composition operators on the space of Bloch functions on the unit ball of a Hilbert space - Miralles, Alejandro (Banach journal of mathematical analysis, 2023)
Let B E be the open unit ball of a complex finite or infinite dimensional Hilbert space E and consider the space B ( B E ) of Bloch functions on B E . Using Lipschitz continuity of the dilation map on B E given by x ↦ ( 1 - ‖ x ‖ 2 ) R f ( x ) for x ∈ B E , where R f denotes the radial derivative of f ∈ B ( B E ) , we study when a composition operator on B ( B E ) is bounded below.